2017
DOI: 10.1002/hrm.21857
|View full text |Cite
|
Sign up to set email alerts
|

Appearing self‐confident and getting credit for it: Why it may be easier for men than women to gain influence at work

Abstract: Appearing self‐confident is instrumental for progressing at work. However, little is known about what makes individuals appear self‐confident at work. We draw on attribution and social perceptions literature to theorize about both antecedents and consequences of appearing self‐confident for men and women in male‐dominated professions. We suggest that performance is one determinant of whether individuals are seen as confident at work and that this effect is moderated by gender. We further propose that self‐conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 110 publications
(181 reference statements)
2
45
0
2
Order By: Relevance
“…These findings are from numerous contexts and stakeholder groups such as CEOs and Board members in businesses (Glass & Cook, ), women and men engineers (Guillén et al, ), women engineers (Singh et al, ), women and men employees in the United Kingdom (Fritz & van Knippenberg, ) and in Germany (Mölders et al, ), “professionally‐employed new mothers in the United States as they transitioned back to work” (Ladge et al, ), and experiments looking at perceived riskiness of hiring women compared to men leaders (Van Esch et al, ). The studies focused on women in contrast to men or system‐level phenomena.…”
Section: Thematic Clusters Of Articles In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…These findings are from numerous contexts and stakeholder groups such as CEOs and Board members in businesses (Glass & Cook, ), women and men engineers (Guillén et al, ), women engineers (Singh et al, ), women and men employees in the United Kingdom (Fritz & van Knippenberg, ) and in Germany (Mölders et al, ), “professionally‐employed new mothers in the United States as they transitioned back to work” (Ladge et al, ), and experiments looking at perceived riskiness of hiring women compared to men leaders (Van Esch et al, ). The studies focused on women in contrast to men or system‐level phenomena.…”
Section: Thematic Clusters Of Articles In This Special Issuementioning
confidence: 99%
“…One answer is influence. Guillén et al () found when women engineers appear to be self‐confident—or “are perceived as being able to meet his/her performance standards, or has a sense of agency at work”—these appearances are “precursor(s) of individual influence in organizations” with career effects. Self‐confidence appearance also needs to be accompanied by prosocial or communal orientations.…”
Section: Thematic Clusters Of Articles In This Special Issuementioning
confidence: 99%
“…For example, a higher prevalence of imposter syndrome is well documented amongst medical students and females medical students are twice as likely to endorse symptoms compared to males [21,22]. Studies in other context showing that the consequences of appearing confident are also different across gender [6,7,23]. Together, these data directly implicate the development of enhanced medical student training to address issues rooted in differences across key aspects of diversity related conflict, providing data for those areas on which to focus.…”
Section: Discussionmentioning
confidence: 99%
“…Institutionalized workplace structures provide formalized support for women. Researchers have found that in terms of exerting influence, women lack confidence because of the gender assessments of their ability (Eagly & Carli, 2007;Guillén, Mayo & Karelaia, 2018;Ridgeway & Correll, 2004). Here, individual-level explanations enhance or hinder women's organizational mobility according to scholars (Cook & Glass, 2014: 92).…”
Section: Institutional Theorymentioning
confidence: 99%